Thursday

July 24, 2014

July 24, 2014

Posted by **Anonymous** on Wednesday, January 6, 2010 at 9:49pm.

- math -
**kayla**, Wednesday, January 6, 2010 at 11:01pmsystems of equations by graphing

- math -
**MathMate**, Thursday, January 7, 2010 at 7:04amI have made some editorial changes to reflect my interpretation of the question:

"If a^2+b^2=2ab,

prove log[(a+b)/2]=(1/2)(loga+logb)"

If a²+b²=2ab, then

a²+b²-2ab=0

(a-b)²=0 after factoring

So we conclude that a=b

Substituting a=b into the left-hand side of the equation:

log[(a+b)/2]

=log((a+a)/2)

=log(a)

The right-hand side:

(1/2)(loga+logb)

=(1/2)(log(a)+log(a))

=log(a)

Therefore:

log[(a+b)/2]=(1/2)(loga+logb)

**Related Questions**

Math - Which of the following is not a property of logarithms? A. log(A - B) = ...

Math - 1. Given the product law of logarithms, prove the product law of ...

math trouble - I have 2 problems I need help with using either substitution or ...

HELP! - I have no idea what the answer to this problem is, I'm given choices but...

Math Algebra 2 - #4. Express the logarithm in terms of log2M and log2N: log2 1/...

algebra 2 - log(base 2)csc(x) = log(base 4)csc(4x^2) I tried doing the log(base ...

Math Algebra 2 - How do I put log in a TI-84 calculator. #1.Express the ...

Math Exam Tuesday - My friend swears by your site so I thought I'd confirm some ...

Math - Apply algebraic reasoning to show that a=b^(loga/logb) for any a,b>0

Math - Apply algebraic reasoning to show that a=b^(loga/logb) for any a,b>0